Chlorhexidine-alcohol versus povidone-iodine as preoperative skin preparation to prevent surgical site infection: a meta-analysis (Faculty of Medicine Universitas Indonesia, 2017)
Background: Surgical site infection remains substantial problems to surgeons and patients as it increases the morbidity, mortality, length of stay, hospital cost, rate of re-admission, and rate of re-surgery. This study aims to compare the use of chlorhexidine-alcohol versus povidone-iodine for preoperative skin preparation to prevent surgical site infection.Methods: The literature search was conducted through the PubMed database on November 2015. Included studies were RCTs with the year of publication up to 2015 which compared the use of chlorhexidine-alcohol versus povidone-iodine in its effectiveness reducing surgical site infection in adult patients. The quality of the study was assessed using Jadad Score. A meta-analysis was conducted in the included study to obtain a pooled estimate of the effect size. The evidence of heterogeneity and publication bias was also assessed.Results: Six RCTs with a total of 2,080 patients were included in the meta-analysis. It showed that the use of chlorhexidine-alcohol was associated significantly with fewer SSIs (pooled risk ratio=0.60 (95% CI=0.45-0.79)) and fewer positive skin culture results (pooled risk ratio, RR=0.38 (95% CI=0.28-0.51)) compared with povidone iodine.Conclusion: Preoperative skin antisepsis with chlorhexidine is more effective than povidone-iodine in preventing surgical site infection.